Ruang Nir-Kata bagi Luka yang Terpendam: Suara Laki-Laki Penyintas Kekerasan Seksual sebagai Sumber Berteologi Trauma - Sariri, Meilina Simon; Rahyuni Daud Pori; Kevin Daniel Simorangkir (Faculty of Theology Duta Wacana Christian University, 2024)
AbstractThis paper offers a wordless space as a term for the wounded space for male survivors of sexual violence. Wordless space is offered as a perspective on trauma theology from the perspective of male survivors ofsexual violence. This perspective departs from the data on sexual violence against men, which is quite high but still lacks attention from various parties. The assumption that men are the perpetrators of sexual violence, social constructions of masculinity and certain theological thinking have resulted in male survivors of sexual violence suppressing the voice of their wounds and limiting the space for the voice of their wounds. The thoughts of Annie Rogers, Cathy Caruth, and Shelly Rambo, in relation to trauma, are used to look at the traumatic experiences of male survivors of sexual violence as well as the basis for wordless space as a perspective in trauma theology. AbstrakTulisan ini menawarkan ruang nir-kata sebagai sebutan bagi ruang luka bagi laki-laki penyintas kekerasan seksual. Ruang nir-kata ditawarkan sebagai perspektif berteologi trauma dari sudut pandang laki-laki penyintas kekerasan seksual. Perspektif ini berangkat dari data kekerasan seksual pada laki-laki berada pada angka yang cukup tinggi namun masih kurang mendapatkan perhatian dari berbagai pihak. Anggapan tentang laki-laki adalah pelaku kekerasan seksual, konstruksi sosial tentang maskulinitas, dan pemikiran teologi tertentu telah mengakibatkan laki-laki penyintas kekerasan seksual memendam suara luka mereka dan membatasi ruang bagi suara luka tersebut. Pemikiran dari Annie Rogers, Cathy Caruth, dan Shelly Rambo, dalam kaitannya dengan trauma, dipakai untuk melihat pengalaman traumatis laki-laki penyintas kekerasan seksual sekaligus landasan bagi ruang nir-kata sebagai perspektif dalam berteologi trauma.